The Parameters of Multilingual Legal Communication in a Globalized World - Sandrini, Peter (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2009)
In law a tendency towards a tighter global embedding of national legislation can be observed. A few historical notes on the evolving of national legal systems will be the basis for the identifi cation of the parameters of international legal communication and the factors influencing legal translation. An attempt at defi ning legal translation from the viewpoint of LSPcommunication leads to a comprehensive overview of the key parameters for legal translation.
Keywords: legal communication; legal translation; communicative parameters; legal systems